2017
DOI: 10.3892/ol.2017.7098
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo model of non‑small cell lung cancer using mouse lung epithelial cells

Abstract: Abstract. Lung cancer is the most common cause of cancer mortality, however, efficient methods to culture, expand and transform lung epithelial (LE) cells have not been established. In the present study, an efficient ex vivo method was applied to recapitulate lung carcinogenesis using mouse LE cells. A Matrigel-assisted three-dimensional culture was used to isolate and selectively expand LE cells from mouse lungs. Purified LE cells were passaged and expanded for at least 2 to 3 months while maintaining epiderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Organoids can be subjected to genetic engineering by viral introduction of shRNA and cDNA. With highly efficient lentiviral gene transduction into murine organoids [87], we demonstrated that the whole processes of multi-step carcinogenesis could be recapitulated for the intestine, lungs and the biliary tract, as subcutaneous tumors in nude mice [88,89,90]. Essentially similar results to earlier in vivo studies were obtained in a significantly shorter period of time, suggesting that this approach might at least partly substitute and complement the conventional gene-targeting approach in modeling carcinogenesis.…”
Section: Patient-derived Cellsmentioning
confidence: 99%
“…Organoids can be subjected to genetic engineering by viral introduction of shRNA and cDNA. With highly efficient lentiviral gene transduction into murine organoids [87], we demonstrated that the whole processes of multi-step carcinogenesis could be recapitulated for the intestine, lungs and the biliary tract, as subcutaneous tumors in nude mice [88,89,90]. Essentially similar results to earlier in vivo studies were obtained in a significantly shorter period of time, suggesting that this approach might at least partly substitute and complement the conventional gene-targeting approach in modeling carcinogenesis.…”
Section: Patient-derived Cellsmentioning
confidence: 99%
“…Histologically, tumor glands were densely packed, while disrupted glands were rarely observed, suggestive of anti‐apoptotic effects by Kras G12D . Our experience in organoid‐based tumorigenesis for the lung, pancreas (Matsuura et al, submitted ) and hepato‐biliary tract (Ochiai et al, submitted ) suggests that emergence of a cystic component is closely associated with Kras G12D . Accordingly, future classification of the nodules might as well include “cyst” in the category of non‐tumorous nodules.…”
Section: An Organoid‐based Carcinogenesis Model For Murine Intestinementioning
confidence: 99%
“…To date, it has been applied to various research fields, including infectious disease models, developmental biology, and epithelial regeneration . We also reported the establishment of murine organoid‐based carcinogenesis models for intestine, lung, hepatobiliary tract, and pancreas . These organoid culture techniques have now become common for patient‐derived samples from diverse types of cancer, which revealed that tumor‐derived organoids basically retained the morphology and genetic aberrations of the original tumors .…”
Section: Introductionmentioning
confidence: 99%